2016
DOI: 10.17221/32/2015-rae
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of composite material reinforced with textile waste from the process of tyres recycling

Abstract: Müller M. (2016): Mechanical properties of composite material reinforced with textile waste from the process of tyres recycling. Res. Agr. Eng., 62: 99-105.The paper deals with the polymeric fibre composite with the reinforcement on the basis of the waste from the process of the tyres recycling. The aim of the research was the use of the material of cleaned textile waste from the process of the tyres recycling. The secondary waste raw material was used as filler in the composite. The subject of performed exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…The textile waste coming from the tires process has been applied, as a discontinuous phase, in two-component epoxy adhesive. The characterization of the prepared samples revealed that the addition of the recovered fibers from the tire recycling determined an increase of the impact strength, but a worsening of the tensile strength and elongation [ 56 ].…”
Section: Recent Applications Of Waste Textiles Into Organic or Inomentioning
confidence: 99%
“…The textile waste coming from the tires process has been applied, as a discontinuous phase, in two-component epoxy adhesive. The characterization of the prepared samples revealed that the addition of the recovered fibers from the tire recycling determined an increase of the impact strength, but a worsening of the tensile strength and elongation [ 56 ].…”
Section: Recent Applications Of Waste Textiles Into Organic or Inomentioning
confidence: 99%
“…Recycling also helps in greening our infrastructures by conserving natural resources, making our infrastructures more durable due to high-performance mixtures, reducing greenhouse gas emissions and air pollution and groundwater contamination [13]. Many researchers researched composite materials reinforced with different textile materials such as textile microfibers waste [14], cotton fibers waste [15], polyester fiber waste [16], woven bamboo fiber [17], rice husk, wheat husk, wood fibers and textile waste fibers [18], Maize Cob and Jute Fiber [19], polyester-cotton fabric [12], cotton, jute, and glass fabric (Masood et al 2018), banana woven fabric 8, paper/jute fabric [20], low-density polyethylene (LDPE) [21], and biodegradable textile waste [22].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there is still a growing share of natural fibers in these systems. These natural fibers suitable substitute synthetic fibers due to their availability and the price [3][4]. It is the substitution, which is friendly to the environment [5].…”
Section: Introductionmentioning
confidence: 99%